2006
DOI: 10.1083/jcb1735oia10
|View full text |Cite
|
Sign up to set email alerts
|

Impaired degranulation but enhanced cytokine production after FcεRI stimulation of diacylglycerol kinase ζ–deficient mast cells

Abstract: Calcium and diacylglycerol are critical second messengers that together effect mast cell degranulation after allergen cross-linking of immunoglobulin (Ig)E-bound Fc RI. Diacylglycerol kinase (DGK) is a negative regulator of diacylglycerol-dependent signaling that acts by converting diacylglycerol to phosphatidic acid. We reported previously that DGK −/− mice have enhanced in vivo T cell function. Here, we demonstrate that these mice have diminished in vivo mast cell function, as revealed by impaired local anap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…However, PMA plus ionomycin stimulation induces a similar level of β‐hexosaminidase release in WT and DGKζ‐deficient BMMCs, suggesting that the defect causing impairment of mast cell degranulation in DGKζ‐deficient BMMCs is proximal to DAG and Ca 2+ . The impairment of mast cell degranulation has been confirmed by measurement of PCA responses, which are much weaker in DGKζ‐deficient mice than in WT mice (77).…”
Section: Regulating Fcɛri Signaling and Mast Cell Function By Dgkζmentioning
confidence: 87%
See 3 more Smart Citations
“…However, PMA plus ionomycin stimulation induces a similar level of β‐hexosaminidase release in WT and DGKζ‐deficient BMMCs, suggesting that the defect causing impairment of mast cell degranulation in DGKζ‐deficient BMMCs is proximal to DAG and Ca 2+ . The impairment of mast cell degranulation has been confirmed by measurement of PCA responses, which are much weaker in DGKζ‐deficient mice than in WT mice (77).…”
Section: Regulating Fcɛri Signaling and Mast Cell Function By Dgkζmentioning
confidence: 87%
“…Using DGKζ‐deficient BMMCs, Olenchock et al (77) investigated how deficiency of this specific DGK isoform may affect mast cell activation. Similar numbers of mast cells have been detected in multiple tissues in DGKζ‐deficient mice as compared with WT mice.…”
Section: Regulating Fcɛri Signaling and Mast Cell Function By Dgkζmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators have suggested that the activation pattern is transient. For example, Olenchock et al showed that upon FCεRI crosslinking, ERK activation peaked at 30 s and declined after 2 min [11]. When RBL-2H3 cells were studied, ERK activation was transient, peaking at 6 min and was completed by 15 min [8,9].…”
Section: Discussionmentioning
confidence: 97%